2019
DOI: 10.1016/j.ejso.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Transverse myocutaneous gracilis flap reconstruction is feasible after pelvic exenteration: 12-year surgical and oncological results

Abstract: Introduction: Pelvic exenteration (PE) is the only curative treatment for certain locally advanced intrapelvic malignancies. PE has high morbidity, and optimal reconstruction of the pelvic floor remains undetermined. Materials and methods: A retrospective chart review was performed at a tertiary university center to assess the surgical and oncological outcomes of 39 PE procedures over a 12-year period. The majority of patients (n ¼ 25) underwent transverse musculocutaneous gracilis (TMG) flap reconstruction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Here, we saw only one partial flap necrosis (<30%) in the MGF group that could be attributed to perfusion problems and resulted in operative debridement and repositioning of the flap. The rates of partial flap loss among MGF (6%) are comparable to those that have been reported for TMG flaps (Kaartinen et al 6%; Kiiski et al 4%) (37,41).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Here, we saw only one partial flap necrosis (<30%) in the MGF group that could be attributed to perfusion problems and resulted in operative debridement and repositioning of the flap. The rates of partial flap loss among MGF (6%) are comparable to those that have been reported for TMG flaps (Kaartinen et al 6%; Kiiski et al 4%) (37,41).…”
Section: Discussionsupporting
confidence: 79%
“…Anatomic studies of the proximal gracilis pedicle illustrated both septocutaneous and myocutaneous perforators traveling in a transverse direction, suggesting the skin island for the MGF should be redesigned in a horizontal fashion (6,36). To date, several authors prefer the horizontal skin island design (transverse myocutaneous gracilis flap, TMG flap) and achieve flap dimensions that are comparable to the vertical flap design (37). Further developments included a bilobed design of the MGF for perineal reconstruction (6).…”
Section: Discussionmentioning
confidence: 99%
“…10 The reconstructive armamentarium includes local, 5,[11][12][13] abdominal (vertical rectus abdominis myocutaneous (VRAM) or vertical deep inferior epigastric perforator), 9,[14][15][16] and thigh-based flaps (gracillis myocutaneous, anterolateral thigh (ALT), and posteromedial thigh). 5,6,[17][18][19][20] Pedicled VRAM are considered the gold standard after APR. This technique, however, is limited by the number and position of ostomies needed and prior abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, successful use of various myocutaneous flaps in the management of perineal wounds has been reported. 7,8 Several studies have reported experiences using the gracilis muscle flap (GMF), 9,10 although most of the results have not been in the setting of TPES. Here, we retrospectively reviewed our seven cases with the aim of evaluating the usefulness of GMF in the reconstruction of large perineal defects following TPES for LRRC in the pelvis.…”
Section: Usefulness Of the Gracilis Muscle Flap For Reconstruction Of...mentioning
confidence: 99%